Improved integrate-and-fire model for RSA - Michele Barbi; Angelo Di Garbo; Rita Balocchi (Mathematical Biosciences and Engineering)
A simple operational model of heart rate variability is described, accounting in particular for the respiratory sinus arrhythmia, and is fitted to some interbeat interval sequences recorded from normal subjects at rest. The model performance is evaluated using a test based on the nonlinear prediction approach. Moreover, a short comparative account of two similar models described in the literature is given.